1,6-Conjugate Additions of Carbon Nucleophiles to 2-[(1E,3E)-4-Arylbuta-1,3-dien-1-yl]-4H-chromen-4-ones - Albuquerque, Hélio (2018)
KGaA, Weinheim The 1,6-conjugate addition of nitromethane to 2-[(1E,3E)-4-arylbuta-1,3-dien-1-yl]-4H-chromen-4-ones was accomplished and led mainly to the corresponding β-(nitromethyl)chromones. (E)-5′-(Nitromethyl)-3′-styryl-[1,1′-biphenyl] -2-ol and 3′-aryl-2′-nitro-5′-(nitromethyl)spiro[chromane-2,1′-cyclohexan]-4-one derivatives were also isolated as minor products from tandem processes, which result from the addition of a second molecule of nitromethane. The nucleophile scope was investigated with malononitrile, acetylacetone, ethyl cyanoacetate, and diethyl malonate, which gave the expected 1,6-addition products; in the last case, it was also possible to isolate a minor product formed through a 1,8-/1,6-addition sequence. Computational calculations provided a rationale for the experimental reactivity of carbon nucleophiles with 2-[(1E,3E)-4-arylbuta-1,3-dien-1-yl] -4H-chromen-4-ones. The further functionalization of some adducts allowed the preparation of new nitrogen-containing heterocyclic compounds, such as new styrylpyrrolidines and new pyrazole and bis(pyrazole) derivatives.